Analytical Hierarchy Process On Supplier Selection Analysis: A Case Study in PT "X" - Sudrajat, Asep; Aprilia Krisna, Kiki; Hertina, Dede (Moneter: Jurnal Keuangan dan Perbankan, 2024)
Business developments and the emergence of many competitors mean that companies must be able to develop and improve their performance. Supplier selection is one of the most important things in maintaining company performance, because selecting the right supplier will not result in losses for the company. This research aims to find out the best strategy that can be implemented by companies, so that companies can choose suppliers who have the best quality among existing suppliers. This research took a sample of companies located in Bandung City, specifically PT "X". Three main criteria have been obtained, namely quality (0.633), price (0.260), and the last one is delivery time (lead time) (0.107), and these three criteria are applied to 4 suppliers. Based on the results of the analysis, Supplier 2 received the highest final score and was ranked number one with a value of 0.537, then Supplier 1 was ranked 2nd with a final value of 0.191, Supplier 3 was ranked 3rd with a final value of 0.131 and Supplier 4 was ranked last with a final value of 0. 13. Therefore, the priority for ordering goods made by PT "X" is ordering Small Angle Assembly +4 Way SAE425-70 products from Supplier 2.